The Shift Analysis on Woman Traditional Underwear Designs in Java and Bali from 1900 until 2000s - Pangestuti, Annisa; Tresnadi, Chandra (Mudra Jurnal Seni Budaya, 2024)
Indonesia is a country that pays attention to Eastern tradition, namely in politeness value either in attitude or socialization. Politeness in fashion considers the importance of the value of politeness in clothing. The politeness limitation in fashion in Indonesia was from the navel to ankles by exploring historically to find out the fashion change, especially in traditional clothing in Indonesia in some periods. This research aimed to trace the chronology of fashion change in traditional women in Indonesia from 1900 until 2000 and to study the fashion change from 1900 until 2000. The research method was historical, with data in figure samples obtained from 1900 until 2000. This research resulted in the chronology of the transformation of fashion change in traditional women's underwear from 1900 until 2000. This research found that fashion shifted from Colonialism to the Reformation. The conventional cloth changed from the initial usage, namely kemben, to bustier. Kemben usage in 1860, camisole usage in 1925, and the old order in 1954 is bustier. The length level of fashion design experienced a decrease. In the colonial period, traditional undergarments covered the breast. Still, in the reformation era, some only lasted until the peak of the breast, initially only from the navel until the ankle, then changed from the breast to the ankle. Technological advances have impacted the freedom to access information included in fashion.